Recovery of an Antioxidant Derived from a Phenolic Diphosphite from Wastewater during the Production of a Polypropylene Compound: A Step towards Sustainable Management (2024)
Organic phosphoester (OPE) antioxidants are currently required due to their contribution to enhancing the quality of polymers, including polypropylene (PP). In this research, an integral methodology is presented for the efficient extraction of bis(2,4-dicumylphenyl) pentaerythritol diphosphite from industrial wastewater. Upon employing the solid-phase extraction (SPE) technique, the recovered compound is subjected to a comprehensive analysis of the recovered compound using high-performance liquid chromatography (HPLC), mass spectrometry (MS), thermal analysis (TGA), Fourier transforms infrared spectroscopy (FTIR), and differential scanning calorimetry (DSC). Subsequently, purified Bis(2,4-dicumylphenyl) pentaerythritol diphosphite was evaluated as a thermooxidative stabilizer after incorporation into PP resins. The relative standard deviation (RSD), Error (Er), linearity (R2), and percentage (%) recovery were less than 2.6, 2.5, more significant than 0.9995, and greater than 96%, respectively, for the inter-day and intra-day tests of the chromatographic method and the SPE. Except for chloroform, which was necessary due to the solubility properties of the investigated analyte, the use of environmentally friendly solvents, such as methanol and acetonitrile, was considered during the development of this research. The OPE extracted from industrial wastewater was characterized by FTIR, UV–Vis, DSC, TGA, and MS, allowing the elucidation of the structure of Bis(2,4-dicumylphenyl) pentaerythritol diphosphite (BDPD). The recovered OPE was mixed with PP resins, allowing it to improve its thermal properties and minimize its thermo-oxidative degradation. Organophosphorus flame retardant (OPE)’ concentration in wastewater is alarming, ranging from 1179.0 to 4709.6 mg L−1. These exceed toxicity thresholds for aquatic organisms, emphasizing global environmental risks. Using a validated solid-phase extraction (SPE) technique with over 94% recovery, the study addresses concerns by removing organic contaminants and supporting circular economy principles. The high economic and environmental significance of recovering BDPD underscores the need for urgent global attention and intervention.